2006
DOI: 10.1149/1.2168379
|View full text |Cite
|
Sign up to set email alerts
|

Microrod and Microtube Formation by Electrodeposition of Metal into Ordered Macropores Prepared in p-Type Silicon

Abstract: Copper and nickel electrodeposition into ordered macropores prepared in p-type silicon has been studied in aqueous solutions containing cupric and nickel ions, respectively. When a macroporous silicon template was cathodically polarized in 0.1 M cupric sulfate solution, copper was deposited preferentially at the pore bottom in the dark, whereas the deposition was found to proceed not only at the pore bottom but also partially on the pore wall under the back side illumination. In contrast, the deposition of nic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
2
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 30 publications
(39 reference statements)
4
43
2
4
Order By: Relevance
“…A platinum film with an average thickness of about 280 nm was formed on the wall surface inside the pores, indicating that cathodic currents were supplied from the InP wall inside the pores. Similar structure has been reported in the case using a conductive porous template such as a Si porous structure [16]. Average thickness of the platinum film is plotted against processing time of the cathodic formation in Fig.…”
Section: Formation Of Platinum/porous Inp Structuressupporting
confidence: 69%
“…A platinum film with an average thickness of about 280 nm was formed on the wall surface inside the pores, indicating that cathodic currents were supplied from the InP wall inside the pores. Similar structure has been reported in the case using a conductive porous template such as a Si porous structure [16]. Average thickness of the platinum film is plotted against processing time of the cathodic formation in Fig.…”
Section: Formation Of Platinum/porous Inp Structuressupporting
confidence: 69%
“…A limited number of studies on the filling of porous silicon with metals by electrodeposition were reported [7][8][9][10][11][12][13][14][15][16] compared with the other non-conducting template such as porous alumina and porous silica. This is because electrodeposition reactions proceed not only at the pore bottom but also on the wall, leading to the complex distribution of electric field and concentration profiles in the pore.…”
Section: Introductionmentioning
confidence: 99%
“…From a different point of view, there are possibilities to form various morphologies of deposits by controlling the electrodeposition reaction on the pore wall. We reported that shapes of deposits could be controlled as rods or tubes in ordered macroporous p-type silicon [13][14][15][16]. The mechanism of the macropore filling depends on various factors, for instance, the equilibrium potential of metal, the depth of the macropore, the supporting electrolyte for electrodeposition and the displacement deposition.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we combine these methods to produce metal filled Si nanopores, that is, metal nanorods in an Si matrix by an electroless process. This simple and low cost process is not only interesting for making such a structure [19,20], but is also favorable to apply ultrahigh-density perpendicular magnetic recording media [21].…”
Section: Introductionmentioning
confidence: 99%